Identifying and Ranking of Competitive Performance Evaluation Criteria of Universities Using Multi-Criteria Decision Making Techniques - badri abasi (پژوهش در نظام‌های آموزشی, 2020)
The purpose of this study is to identify and rank the criteria for assessing the competitive performance of the university using multi-criteria decision-making techniques. The present study is descriptive and the research community consists of 15 people who are knowledgeable in the field of higher education and science and technology policy. A library collection method and a data gathering tool was a researcher-made questionnaire consisting of 6 criteria and 53 sub-criteria based on a comprehensive review of the literature related to university performance evaluation indicators. The identification, ranking and validation of the tool using AHP and TOPSIS Techniques showed that the criteria of compilation of competitive strategies, management and leadership of the university and the relationship with higher education stakeholders ranked first to third in the indicators of competitive performance assessment. Allocate.Finally, it is suggested that policy makers in higher education, in planning the development of performance indicators of the university, will propose a multidisciplinary multidisciplinary outline of the proposed competitive performance indicators of the present study and, in regular and regular meetings, establish competitive culture in the Pyramid of Higher Educational Institution.